Characteristic of Virulence and Parameters of Mixed Biofilm Formed by Carbapenem-Resistant Pseudomonas aeruginosa and Proteus mirabilis Strains Isolated from Infected Chronic Wounds - Jana Wełna; Marta Napiórkowska-Mastalerz; Michał Cyrankiewicz; Tomasz Bogiel; Joanna Kwiecińska-Piróg (Pathogens)
A biofilm is a group of bacterial cells in the polysaccharide matrix bonded to the surface (biotic or abiotic). Clinicians now realize that most infections are biofilm-related. Biofilm infections are often induced by more than one bacterial species. The aim of this study is to characterize a mixed biofilm composed of Pseudomonas aeruginosa and Proteus mirabilis strains. Forty-six isolates derived from chronic wound infections were cultivated to establish mature biofilms. The biofilm biomass and cell viability were measured by colorimetric assays. P. aeruginosa strains were tested for the presence of virulence and biofilm-related genes. The quorum sensing assay using the biosensor strain was also performed. A mixed biofilm of P. aeruginosa and P. mirabilis was visualized using fluorescence microscopy. Four groups of P. aeruginosa and P. mirabilis pairs, also visualized with fluorescence microscopy, were distinguished based on the biofilm biomass growth and metabolic activity loss. The exoY gene observed among P. aeruginosa isolates was connected to the metabolic activity loss of the biofilm. Generally, the interactions between P. aeruginosa and P. mirabilis species are not uniform. It is crucial to further research the interactions between microorganisms in biofilms. This may provide information on the mechanisms of biofilm formation in the complicated chronic wound environment.